Epidemiological, etiological, and serological characteristics of hand, foot, and mouth disease in Guizhou Province, Southwest China, from 2008 to 2023. - Fajin Li; Dan Wang; Fei Su; Suye Zhao; Jun Guo; Fumin Zhang; Xueqin Ran; Jiafu Wang; Shijun Li (PLoS Neglected Tropical Diseases)
Background Hand, foot, and mouth disease (HFMD) is caused by more than 20 different enteroviruses (EVs). The predominant EV serotypes of HFMD have been continuously changing in recent years. Guizhou Province has reported higher rates of severe and fatal cases of HFMD. However, comprehensive studies on its epidemiology, etiology, and serological characteristics have remained limited in recent years. Methods We collected epidemiological and laboratory data from HFMD cases between 2008 and 2023, analyzing the data by age, gender, disease severity, and EV serotypes. Clinical samples from these cases were collected to isolate EVs. The VP1 gene was amplified from isolates of enterovirus A71 (EV-A71), coxsackievirus A16 (CV-A16), coxsackievirus A6 (CV-A6), and coxsackievirus A10 (CV-A10), and the sequences were analyzed. We collected 432 serum samples from healthy individuals from 2019 to 2022 to assess antibodies against CV-A6, CV-A10, CV-A16, and EV-A71 of HFMD. Results A total of 513,143 HFMD cases were reported in Guizhou Province from 2008 to 2023, including 9052 (1.76%) severe cases and 193 (0.038%) deaths. In laboratory-confirmed cases, EV-A71 was the dominant serotype from 2008 to 2012; other EVs became predominant from 2013 to 2018, and CV-A6 predominated in 2019, 2022, and 2023. Interestingly, novel epidemiological patterns of CV-A6 infection were observed, with a high incidence every other year in various cities since 2019. Among 432 healthy individuals, the overall seroprevalence rates of CV-A6, CV-A10, CV-A16, and EV-A71 were 62.04%, 54.17%, 54.63%, and 64.35%, respectively. Additionally, over 70% of the participants had neutralizing antibodies (NtAbs) against at least two types of these enteroviruses. Phylogenetic analysis revealed that CV-A16 isolates clustered into the B1a or B1b evolutionary branches, while EV-A71, CV-A6, and CV-A10 isolates belonged to the C4a, D3a, and C subgenotypes, respectively. Conclusions This results indicate differences in the incidence of major HFMD pathogens across years, regions, and populations. Other EVs, predominantly CV-A6, have become the main pathogens causing HFMD since 2019. CV-A6, CV-A10, CV-A16, and EV-A71 exhibited relatively high seroprevalence rates. Currently, there is an urgent need to develop multivalent vaccines and implement effective measures to reduce incidence of HFMD.